Mental Health Status of Psychogeriatric Patients During the 2019 New Coronavirus Disease (COVID-19) Pandemic and Effects on Caregiver Burden - Penteado, Camila T.; Loureiro, Julia C.; Pais, Marcos V.; Carvalho, Cláudia L.; Sant'Ana, Lívea F. G.; Valiengo, Leandro C. L.; Stella, Florindo; Forlenza, Orestes V. (Frontiers in Psychiatry, 2020)
Introduction: There is a growing awareness about the noxious effects of the COVID-19 pandemic on the mental health of the elderly. However, there is limited information from clinically-driven research. The objectives of the present study were to examine the magnitude of psychiatric symptoms and to determine their association with caregiver distress, in a cross-section of community-dwelling older adults and a sub-sample of aging adults with Down syndrome (DS) attending a psychogeriatric service in São Paulo, Brazil. Method: Telephone-based interviews and electronically-filled self-assessment questionnaires were used to collect information from patients and caregivers, addressing their impressions and concerns about the pandemic and related effects on the patient’s emotional state and behaviour. Clinical information was obtained from hospital charts, medical records and psychometric tests administered through telephone interviews (Hospital Anxiety and Depression Scale, HAD, and Neuropsychiatric Inventory Questionnaire, NPI-Q). Results: We included 100 consecutive participants, being 71 older adults with psychogeriatric/neurocognitive disorders, and 29 aging-adults with DS. Higher HAD and NPI-Q scores were significantly associated with caregiver distress (p<0.05) in both groups. Correlation analyses indicated strong, positive associations between caregiver burden and scores in HAD-anxiety and HAD-depression scales in the sub-samples of euploid and DS subjects. Higher NPI-Q scores in the former group were also correlated with caregiver distress, with stronger associations for neuropsychiatric symptoms. Similar findings were observed among DS subjects. ANOVA tests indicated significant associations between NPI-Q scores and caregiver distress among dementia patients, as well as with HAD scores. Similar results were found after Multiple Linear Regressions, as such: among the elderly subsample, higher scores in HAD-A (p=0,002) and HAD-D (p=0,001) predict a significant impact on caregiver burden (p<0,00001, R² 0,46); taking into consideration caregiver burden as dependent variable and NPI-Q total score as independent variable, we obtained significant strong prediction values for either DS (p<0,00001, R² 0,95) or Elderly adults (p<0,00001, R² 0,88). Conclusion: During the COVID-19 pandemic, patients with neurocognitive disorders present with clinically relevant neuropsychiatric symptoms, with significant impact on caregiver distress. Apathy, aberrant motor behavior, sleep disorders, and psychoses were the main psychopathological domains, which had determined the caregiver burden worsening.